The complete guide to motorcycle mechanics (Prentice-Hall Career & Technology, 1994)
For courses in Motorcycle Mechanics. Complete and comprehensive introductory textbook for a one semester or year program in motorcycle mechanics. This expanded and updated text reference is sponsored by the leading school for training motorcycle mechanics.